2018
DOI: 10.1093/mnras/sty2752
|View full text |Cite
|
Sign up to set email alerts
|

Studying temporal variability of GRS 1739–278 during the 2014 outburst

Abstract: We report a discovery of low-frequency quasi periodic oscillation at 0.3-0.7 Hz in the power spectra of the accreting black hole GRS 1739-278 in the hard-intermediate state during its 2014 outburst based on the NuSTAR and Swift/XRT data. The QPO frequency strongly evolved with the source flux during the NuSTAR observation. The source spectrum became softer with rising QPO frequency and simultaneous increasing of the power-law index and decreasing of the cut-off energy. In the power spectrum, a prominent harmon… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 112 publications
(158 reference statements)
0
5
0
Order By: Relevance
“…As noted in Mereminskiy et al (2021), an X-ray source is reported in the XMM Newton Slew Survey catalog (Saxton et al 2008), within the ART-XC localization, as XMMSL2 J181414.6-225613. The reported location of the XMM Slew Survey source, along with its uncertainty, is shown in the NIR image in Figure 1.…”
Section: X-ray Coverage From Surveysmentioning
confidence: 86%
See 2 more Smart Citations
“…As noted in Mereminskiy et al (2021), an X-ray source is reported in the XMM Newton Slew Survey catalog (Saxton et al 2008), within the ART-XC localization, as XMMSL2 J181414.6-225613. The reported location of the XMM Slew Survey source, along with its uncertainty, is shown in the NIR image in Figure 1.…”
Section: X-ray Coverage From Surveysmentioning
confidence: 86%
“…A preliminary analysis of the X-ray spectra suggested a heavily absorbed power-law spectrum for SRGA J181414.6-225604 (Bult & Gendreau 2021;Heinke et al 2021;Mereminskiy et al 2021). Bult & Gendreau (2021) also noted a low-energy excess in the NICER spectra, which was attributed to a possible unrelated source in the field of view.…”
Section: Broadband Spectral Analysismentioning
confidence: 98%
See 1 more Smart Citation
“…The reflected component of the hard emission presumably associated with an accretion disk whose inner radius must reach the innermost stable orbit was observed in the source's spectrum, but the disk component itself was not recorded in the spectrum. Mereminskiy et al (2019) performed a detailed timing analysis of the NuSTAR data, based on which QPOs at frequencies 0.3-0.7 Hz were detected in the variability power spectrum for GRS 1739-278. Based on data from the MAXI monitor, Wang et al (2018) showed that the system passed back from the high/soft to low/hard state in November-December 2014.…”
Section: Grs 1739-278mentioning
confidence: 99%
“…When fitting the spectra, we used typical models describing the source's spectrum: (1) in the low/hard state-a power law with a high-energy cutoff and lowenergy absorption, phabs*cutoffpl (or in the case of fitting only the Swift/XRT data-a power law and low-energy absorption, phabs*powerlaw); (2) in the intermediate states-a power law with a high-energy cutoff, a multitemperature accretion disk, and lowenergy absorption, phabs*(cutoffpl + diskbb) (or in the case of fitting only the Swift/XRT data-a power law, a multitemperature accretion disk, and low-energy absorption, phabs*(powerlaw + diskbb)); (3) in the high/soft state-a multitemperature accretion disk and low-energy absorption, phabs*diskbb, or the previous model, phabs*(powerlaw + diskbb). The quality of the available data does not allow us to apply the more complex spectral model including the reflection of Comptonized radiation from the accretion disk that was used in fitting the NuSTAR data (Miller et al 2015;Mereminskiy et al 2019).…”
Section: Spectral Analysis During the 2014 Outburstmentioning
confidence: 99%